Development of high silicon dual phase austempered ductile iron - Basso, Alejandro Daniel (2015)
This work deals with the feasibility of obtaining Austempered Ductile Iron with Dual Phase structures (DPADI) through heat treatment, starting from different as-cast microstructures. The mechanical properties on these microstructures were evaluated. DPADI microstructures were obtained by adding different tenors of silicon (2.4% to 4.2%) to the melts and keeping the other alloying elements constant. The study focused on the determination of the time required to achieve the percentages of equilibrium phases (ferrite and austenite) at different temperatures in the intercritical temperature interval as a function of the starting as cast microstructure. The results showed that, as the silicon content increases, higher amount of ferrite is present in the as cast structure, and the time required to reach the thermodynamic equilibrium phases in the intercritical temperature interval is markedly reduced. Similarly, for a constant chemical composition, as the intercritical austenitizing temperature increases, the time required to reach the quantities of the equilibrium phases decreases. Regarding mechanical properties, the tests revealed that, as expected, as intercritical austenitising temperature increases so do tensile strength and hardness due to the higher ausferrite content in the DPADI matrix. These results indicate that high silicon Ductile Iron (with Si content higher than 3%) with a mostly ferritic microstructure in as cast conditions yields DPADI microstructures able to dispense with prior annealing heat treatments since the time required to reach the phase equilibrium percentages is compatible with the industrial practice and the mechanical properties are similar as compared to DPADI structures deriving from fully ferritic matrices.